Baseline and on-treatment serum bicarbonate, intensive blood pressure lowering, and mortality: the Systolic Blood Pressure Intervention Trial (SPRINT). (25th November 2020) - Pareek, M; Byrne, C; Vaduganathan, M; Biering-Sorensen, T; Krogager, M.L; Kragholm, K.H; McCullough, M; Desai, N.R; Olsen, M.H; Bhatt, D.L
Abstract: Background: Low bicarbonate levels are associated with higher mortality among patients who are hospitalized or have chronic kidney disease. However, the relationship between bicarbonate and mortality among outpatients on antihypertensive treatment is unclear. Purpose: To assess the relationship between serum bicarbonate levels, treatment response to intensive blood pressure lowering, and mortality. Methods: SPRINT was a randomized, controlled trial in which 9, 361 individuals ≥50 years of age, at high cardiovascular (CV) risk, but without diabetes, and a systolic blood pressure (BP) 130–180 mmHg, were randomized to intensive (target systolic BP <120mmHg) or standard antihypertensive treatment (target systolic BP <140mmHg). Patients with an estimated glomerular filtration rate <25 ml/min/1.73 m 2 or end-stage renal disease were excluded. Serum chemistry was drawn at baseline, prespecified intervals, and at close out. We defined on-treatment bicarbonate as the last measurement available for each participant. We then examined the prognostic implications (for death from any cause and death from CV causes) of baseline and on-treatment bicarbonate, using restricted cubic splines, unadjusted and adjusted for demographic, clinical, and laboratory variables. Finally, we explored the effects of intensive blood pressure lowering across the spectrum of bicarbonate using interaction analysis. Results: A total of 9, 334 (99.7%) individuals had a bicarbonate measurement available at baseline and 9, 232 (98.6%) had at least one measurement after baseline. Mean baseline bicarbonate was similar between the two study groups (26.3 mmol/l in both; P=0.84), as was on-treatment bicarbonate (25.2 mmol/l in both; P=0.51). Median follow-up was 3.3 years (range 0–4.8), with 365 deaths from any cause (3.9%) and 102 deaths from CV causes (1.1%) recorded during the study period. Baseline and on-treatment bicarbonate both displayed a significant, U-shaped association with death from any cause (adjusted overall trend, P<0.05; non-linearity vs. linearity, P<0.05). Although both were significantly associated with death from CV causes in unadjusted analysis, the significance was lost upon multivariable adjustment (P>0.05) (Figure). Low baseline bicarbonate was significantly associated with death from any cause (<23 vs. 23–29 mmol/l, adj. hazard ratio (HR) 1.45, 95% confidence interval (CI), 1.06–2.00; P=0.02), but high baseline bicarbonate was not (>29 vs. 23–29 mmol/l; P=0.84). Conversely, both low (adj. HR 1.50, 95% CI, 1.14–1.97; P=0.004) and high (adj. HR 4.77, 95% CI, 3.49–6.52; P<0.001) on-treatment bicarbonate was significantly associated with death from any cause. Bicarbonate did not modify the efficacy of intensive blood pressure lowering (P>0.05). Conclusions: Baseline and on-treatment serum bicarbonate levels both displayed a U-shaped association with the risk of death. The association was not affected by intensive vs. standard blood pressure lowering. Funding Acknowledgement: Type of funding source: None